2021
DOI: 10.1101/2021.11.09.467810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robust and generalizable segmentation of human functional tissue units

Abstract: The Human BioMolecular Atlas Program aims to compile a reference atlas for the healthy human adult body at the cellular level. Functional tissue units (FTU, e.g., renal glomeruli and colonic crypts) are of pathobiological significance and relevant for modeling and understanding disease progression. Yet, annotation of FTUs is time consuming and expensive when done manually and existing algorithms achieve low accuracy and do not generalize well. This paper compares the five winning algorithms from the “Hacking t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The improved spatial resolution extends applicability of ProteomEx as it is more biologically relevant for analysis of heterogeneity of biological tissues. For example, ~100 µm resolution is more appropriate for analysis of functional tissue units (FTU) 38 , e.g., renal glomeruli [39][40][41] , colonic crypts 39 , human lung blood vessels 36 , which are typically limited by 100 µm in size. Furthermore, Piehowski et al demonstrated that 100 µm resolution was sufficient to characterize region-specific bioactivity and unique tissue microenvironments within the mouse Wnt5a-null uterine tissue 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The improved spatial resolution extends applicability of ProteomEx as it is more biologically relevant for analysis of heterogeneity of biological tissues. For example, ~100 µm resolution is more appropriate for analysis of functional tissue units (FTU) 38 , e.g., renal glomeruli [39][40][41] , colonic crypts 39 , human lung blood vessels 36 , which are typically limited by 100 µm in size. Furthermore, Piehowski et al demonstrated that 100 µm resolution was sufficient to characterize region-specific bioactivity and unique tissue microenvironments within the mouse Wnt5a-null uterine tissue 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, the Human BioMolecular Atlas Program (HuBMAP) conducted a Kaggle competition 10,11 that focussed exclusively on segmentation of renal glomeruli in PAS stained histological images of kidney tissue, engaging 1,200 teams from 60 countries.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, the Human BioMolecular Atlas Program (HuBMAP) conducted a Kaggle competition 10,11 that focussed exclusively on segmentation of renal glomeruli in PAS stained histological images of kidney tissue, engaging 1,200 teams from 60 countries. The winning model from this competition was validated and productized in the HuBMAP data portal; it is now being run on all kidney tissue data at scale.…”
Section: Introductionmentioning
confidence: 99%